2014
DOI: 10.4238/2014.january.14.10
|View full text |Cite
|
Sign up to set email alerts
|

PTGS2 gene polymorphism -765G>C is associated with coronary artery disease: a meta-analysis

Abstract: ABSTRACT. Previous studies focusing on the association of PTGS2 polymorphism -765G>C with coronary artery disease (CAD) have failed to reach the same conclusion. In the present study, we performed a meta-analysis to systematically summarize the possible association between PTGS2 polymorphism -765G>C and the risk of CAD. We conducted a search of case-control studies on the associations of PTGS2 with susceptibility to CAD in PubMed, EMBASE, and Chinese National Knowledge Infrastructure databases. Data from eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…A meta-analyses of 22 studies including 3,502 CAD patients and 3,071 controls suggested that the angiotensin II receptor, type 1 gene A1166C polymorphism might be a genetic marker for the development of CAD in Chinese populations, especially in the context of studies with northern and older subjects [ 24 , 25 ]. A meta-analyses of 11 studies involving 22,584 subjects showed that PTGS2 -765G/C was associated with a decreased risk of CAD [ 26 ]. A meta-analyses of ten studies with 4,413 patients found that apolipoprotein M T-778C polymorphism was associated with serum lipid levels and the risk of CAD in the Chinese population [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analyses of 22 studies including 3,502 CAD patients and 3,071 controls suggested that the angiotensin II receptor, type 1 gene A1166C polymorphism might be a genetic marker for the development of CAD in Chinese populations, especially in the context of studies with northern and older subjects [ 24 , 25 ]. A meta-analyses of 11 studies involving 22,584 subjects showed that PTGS2 -765G/C was associated with a decreased risk of CAD [ 26 ]. A meta-analyses of ten studies with 4,413 patients found that apolipoprotein M T-778C polymorphism was associated with serum lipid levels and the risk of CAD in the Chinese population [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…e former, which is structurally expressed in most normal tissues, is a housekeeping enzyme responsible for a variety of physiological functions and is involved in the formation of thromboxane A2. e latter is rarely expressed in normal tissues but is rapidly induced by cytokines and growth factors [29]. COX-2 is involved in angiogenesis, inhibition of apoptosis, and suppression of the immune response, which are closely associated with CHD.…”
Section: Discussionmentioning
confidence: 99%